RETRACTED: Sugarcane Derived Polyphenol Feed Additive Supplemented to the Wheat Diet Improved Broiler Performance - Sekh, N; Oshea, C (Nepalese Veterinary Journal, 2023)
This article was retracted on 4th March 2025. It was published without permission from the authorities at the authors' institution.